Evaluation of change in emergency care knowledge and skills among front-line healthcare providers in Ukraine with the Basic Emergency Care course: a pretest/post-test study. Issue 6 (14th June 2022) - Kivlehan, Sean M; Allen, Amy; Viun, Olha; Makarov, Dmitry A; Schnorr, Daniel; Patel, Sonny; Ryzhenko, Sergii A; Pham, Phuong; Erickson, Timothy B
Abstract : Objective: Evaluate the change in participant emergency care knowledge and skill confidence after implementation of the WHO-International Committee of the Red Cross (ICRC) Basic Emergency Care (BEC) course. Design: Pretest/post-test quasi-experimental study. Setting: Mechnikov Hospital in Dnipro, Ukraine. Participants: Seventy-nine participants engaged in the course, of whom 50 (63.3%) completed all assessment tools. The course was open to healthcare providers of any level who assess and treat emergency conditions as part of their practice. The most common participant profession was resident physician (24%), followed by health educator (18%) and prehospital provider (14%). Interventions: The 5-day WHO-ICRC BEC course. Primary and secondary outcome measures: Change in pre-course and post-course knowledge and skill confidence assessments. Open-ended written feedback was collected upon course completion and analysed for common themes. Results: Participant knowledge assessment scores improved from 19 (IQR 15–20) to 22 (IQR 19–23) on a 25-point scale (p<0.001). Participant skill confidence self-assessment scores improved from 2.5 (IQR 2.1–2.8) to 2.9 (IQR 2.5–3.3) on a 4-point scale (p<0.001). The most common positive feedback themes were high-quality teaching and useful skill sessions. The most common constructive feedback themes were translation challenges and request for additional skill session time. Conclusions: This first implementation of the WHO-ICRC BEC course for front-line healthcare providers in Ukraine was successful and well received by participants. This is also the first report of a BEC implementation outside of Africa and suggests that the course is also effective in the European context, particularly in humanitarian crisis and conflict settings. Future research should evaluate long-term knowledge retention and the impact on patient outcomes. Further iterations should emphasise local language translation and consider expanding clinical skills sessions.